Undervaccination with diphtheria, tetanus, and pertussis vaccine: National trends and association with pertussis risk in young children - Wan-Ting Huang; Hui-Chen Lin; Chin-Hui Yang (Taylor & Francis Group, 2017)
Background: The high coverage for ≥3 pertussis vaccine doses among Taiwanese children might not imply timely vaccination. Recently, resurgence of pertussis and challenges with availability of DTaP-IPV-Hib prompted this study. Methods: In the 1996-2012 national birth cohort, we calculated the prevalence and days of undervaccination against pertussis by age 36 months. We also compared the odds of undervaccination in each laboratory-confirmed pertussis patient at ages 3-35 months with sex-, residence-, and age-matched controls from the general population, using conditional logistic regression. Results: The prevalence of undervaccination was 60.6% (median 16 days) and decreasing (p < 0.0001). Among 145 cases and 2,900 controls, 58 (40.0%) and 721 (24.9%) were undervaccinated (OR 2.28, 95% CI 1.57-3.31). The attributable risk percent was 22.5% (95% CI 14.5-27.9). Conclusions: Undervaccination was decreasing. Approximately up to one-fifth pertussis cases in children aged 3-35 months could have been prevented with on-time vaccination.